Teaching in England post-1988 : reflections and career histories - Woodhouse, Joan (Emerald points., 2023)
There is insufficient research focusing on the perspective of teachers nearing the end of their working lives, and even less offering career length studies on the changes in England over the past few decades. 1988 saw the start of substantive policy shift with the Education Reform Act, and the following years have seen an unprecedented pace and rate of policy shifts. Joan Woodhouse explores the career-histories and reflections of teachers, and how their teaching practices and approach to their work were impacted by the ever-evolving landscape. The insights are critical to understanding this era of reform directly from those who have experienced and implemented the changes. Drawing on in-depth interviews with teachers, Teaching in England Post-1988 affords new understandings of an under-researched group, bringing to light experiences of implementing reform in schools. It raises questions about why, given the pressure they faced, teachers remained in the profession when so many of their peers had quit ahead of retirement age. Presenting a conceptual model explaining career-long teachers' longevity, Teaching in England Post-1988 provides context to help current and future governments develop policy and strategies to reverse the trend of attrition, addressing the much-discussed teacher and headteacher shortage. This is also essential reading for educational researchers and teacher educators.